2014
DOI: 10.1021/ol500310u
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Suzuki–Miyaura Coupling of Arylboronate Esters: Transmetalation with (PN)CuF and Identification of Intermediates

Abstract: An efficient Cu(I)-catalyzed Suzuki-Miyaura reaction was developed for the coupling of aryl- and heteroarylboronate esters with aryl and heteroaryl iodides at low catalyst loadings (2 mol %). The reaction proceeds under ligand-free conditions for aryl-heteroaryl and heteroaryl-heteroaryl couplings. We also conducted the first detailed mechanistic studies by synthesizing [(PN-2)CuI]2, [(PN-2)CuF]2, and (PN-2)CuPh (PN-2 = o-(di-tert-butylphosphino)-N,N-dimethylaniline) and demonstrated that [(PN-2)CuF]2 is the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 53 publications
3
80
0
2
Order By: Relevance
“…The crude product was purified using column chromatography (n-hexane:EtOAc = 80:1) to give as a colorless oil; yield: 3 c 39.9 mg (80%). [20] A mixture of 2-iodotoluene (59.6 mg, 0.25 mmol) and 4-methoxyphenylmagnesium bromide (0.5 M, 0.64 mL, 0.32 mmol, 1.3 equiv.) in THF (0.56 mL) was heated at 75 8C for 3 h in the presence of SANi.…”
Section: Icp-ms Analysismentioning
confidence: 99%
“…The crude product was purified using column chromatography (n-hexane:EtOAc = 80:1) to give as a colorless oil; yield: 3 c 39.9 mg (80%). [20] A mixture of 2-iodotoluene (59.6 mg, 0.25 mmol) and 4-methoxyphenylmagnesium bromide (0.5 M, 0.64 mL, 0.32 mmol, 1.3 equiv.) in THF (0.56 mL) was heated at 75 8C for 3 h in the presence of SANi.…”
Section: Icp-ms Analysismentioning
confidence: 99%
“…We recently reported that a combination of the ligand PN (Table 1) and CuI generated active catalysts that enabled the cross‐coupling of aryl silicon8a and aryl boron9a reagents with aryl iodides. As part of our efforts to expand the scope of Cu I ‐catalyzed coupling processes for CC bond formation, we discovered that PN /CuI was an efficient catalyst for the coupling of triphenylindium with para ‐iodotoluene and afforded the product in 87 % yield without requiring a base (yield determined by GC; Table 1, entry 1).…”
Section: Cross‐coupling Of Triphenylindium With Para‐iodotoluene[a]mentioning
confidence: 99%
“…Unfortunately, these strongly basic nucleophiles are poorly tolerant of electrophilic and protic functional groups and are often accompanied by isomerization, generating byproducts when the temperature of these reactions is not carefully controlled. Beyond these seminal reports, there are additional isolated examples using Kumada 8 or Negishi 9 reagents; however, these do not represent a unified strategy for tertiary cross-couplings. Particularly from a diversification perspective, approaches using these sensitive, pyrophoric reagents are wholly impractical when applied to a wide array of tertiary nucleophiles paired with an equally broad palette of aryl electrophiles.…”
mentioning
confidence: 99%
“…Electron-poor ( 19–23 , 25 ), electron-rich ( 24 ) and heteroaryl halides ( 20 ) all proved viable. Unfortunately, this rather niche reactivity was not unprecedented 17,9a and by no means represented a general solution to tertiary radical coupling.…”
mentioning
confidence: 99%